Lingkungan Kerja dan Kepuasan Kerja Pengaruhnya Terhadap Motivasi Serta Dampaknya Pada Kinerja Pegawai - Adriani, Evi; Surono, Yunan; Budiningtyas, Dwi Putri; Maududi, Said Al; Azrianto, Azrianto; Fahmi, Ali; Hutabarat, Zuhri Saputra (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
The aim of this research is to analyze the influence of the work environment and job satisfaction through simultaneous and partial motivation on the performance of employees of the National and Political Unity Agency in East Tanjung Jabung Regency. This research uses descriptive and verification analysis methods. Descriptive analysis is used to describe the characteristics of respondents and research variables without testing. This research uses a census method, namely all employees at the National and Political Unity Agency in East Tanjung Jabung Regency. The data analysis technique used is path analysis, with the help of the SPSS version 22.0 software program. The results of this research show that the independent variables, namely work environment and job satisfaction, have a positive and significant effect on motivation and have a positive impact on employee performance. This proves that by improving the work environment and job satisfaction, employee motivation will also increase which will have an impact on increasing employee performance. This research concluded that the work environment and job satisfaction and through motivation partially had a positive effect on employee performance at the National and Political Unity Agency in East Tanjung Jabung Regency.